Oral health knowledge and practices among elementary pupils attending Saint Louis College, City of San Fernando, La Union, The Philippines - Fadare, Ayoade Stephen; Daniel, BP; Fadare, CM; ADAMU, VE (Orapuh Journal, 2021)
Introduction The mouth and rest of the body are intricately connected. Whatever affects the health of the mouth may also affect general health. And, sometimes, general health is reflected in the mouth. Because of this, it is important to keep the mouth clean and healthy to prevent common oral diseases, especially, among children who live in developing countries. Purpose The purpose of this study was to assess oral health knowledge and practices among elementary pupils attending Saint Louis College in the City of San Fernando, La Union, The Philippines. Materials and Methods This was a descriptive study. Data were collected from 293 pupils of grade 4 to 6 in the College that were selected using purposive sampling technique and studied, using the questionnaire. The questionnaire was validated by four external dental experts and was subjected to pilot testing. Data collected were analysed using descriptive statistics of frequencies, percentages, and mean scores. Results The study found that most of the pupils manifested satisfactory knowledge about the causes (87.23%) and preventive measures (86.21%) of oral diseases but moderately practiced oral hygiene disciplines (55.80%). These results inferred that oral health knowledge concerning the causes and preventive measures of oral diseases were identified as strengths, while oral hygiene practices were found to constitute areas of weaknesses. Conclusion It is imperative for the parents of the respondents, the school dentist and teachers to jointly develop a way of making sure that the pupils translate their knowledge into practice.